2010
DOI: 10.5194/aab-53-589-2010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of genotype on the chemical and fatty acid composition of the <i>Quadriceps</i> femoris muscle in extensively fattened lambs

Abstract: The aim of the experiment was to define the effect of a Suffolk-sired genotype on the chemical composition and fatty acid profile of the Quadriceps femoris muscle in fattened lambs reared under organic farming conditions. Three different genotypes of Suffolk-sired crossbreds were included in the experiment: F1 Suffolk-Charollais (SF 50 CH 50, n=10), F11 Suffolk-Charollais (SF 75 CH 25, n=10) and F1 Suffolk-Improved Walachian (SF 50 IW 50, n=10). The genotype did not have any effect on age at slaughter, average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
2
7
1
Order By: Relevance
“…A supply of α-linolenic acid in the diet increased EPA and DPA in the plasma and tissues of animals. In this trial, the AI was lower than values reported previously in other studies (Ulbricht and Southgate, 1991;Zapletal et al, 2010) for lamb meat, but similar to values reported by Nasri et al (2011) for Barbarine lambs. The Δ 5 desaturase plus Δ 6 desaturase index was higher (P < 0.01) in lambs grazing on pasture, probably because there is a higher supply of C18:3n-3, which affects the activity of enzymes implicated in the elongation of C18:3n-3 and C18:2n-6 to long PUFAs (Dal Bosco et al, 2014).…”
Section: Resultssupporting
confidence: 87%
“…A supply of α-linolenic acid in the diet increased EPA and DPA in the plasma and tissues of animals. In this trial, the AI was lower than values reported previously in other studies (Ulbricht and Southgate, 1991;Zapletal et al, 2010) for lamb meat, but similar to values reported by Nasri et al (2011) for Barbarine lambs. The Δ 5 desaturase plus Δ 6 desaturase index was higher (P < 0.01) in lambs grazing on pasture, probably because there is a higher supply of C18:3n-3, which affects the activity of enzymes implicated in the elongation of C18:3n-3 and C18:2n-6 to long PUFAs (Dal Bosco et al, 2014).…”
Section: Resultssupporting
confidence: 87%
“…The obtained values of AI and TI could suggest a decrease in the nutritional quality of lamb meat as a result of diet supplementation with β-1,3/1,6-D-glucan, but the above observations were not confirmed by statistical analysis. In our study, AI and TI values were higher than those reported by Zapletal et al (25), and the cited authors attributed their findings to genotype effects.…”
Section: Discussioncontrasting
confidence: 74%
“…This resulted in a significant decrease in UFA levels as well as a drop in the UFA/SFA ratio, which is undesirable from the point of view of nutritional quality (21,24,25 (23), AI and TI values are more reliable indicators of atherogenicity and thrombogenicity than the PUFA/SFA ratio. Not all SFA are hypercholesterolemic, and in addition to PUFA, MUFA also demonstrate protective activity, although to a smaller extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth intensity of lambs before weaning and after weaning significantly affects the economics of farming (Petr et al, 2009;Pajor et al, 2008;2009a;Wolfová et al, 2009;Komprda et al, 2012;Svitáková et al, 2014;Koutná et al, 2016). The growth is affected by many factors where the most important are the breed, nutrition, sex, litter size, management, biotic stress, health and age of mothers (Kuchtík and Horák, 2007;Dobeš et al, 2007;Hošek et al, 2008;Pajor et al, 2007;2009b;Kuchtík et al, 2010;Zapletal et al, 2010;Štolc et al, 2011;Ptáček et al, 2013;Lupi et al, 2015;Waheed et al, 2015;Aguirre Riofrio et al, 2016;Mellado et al, 2016;Moreira et al, 2016;Sieklicki et al, 2016).…”
Section: Introductionmentioning
confidence: 99%